2019
DOI: 10.1158/1078-0432.ccr-18-3421
|View full text |Cite
|
Sign up to set email alerts
|

Breast Phyllodes Tumors Recruit and Repolarize Tumor-Associated Macrophages via Secreting CCL5 to Promote Malignant Progression, Which Can Be Inhibited by CCR5 Inhibition Therapy

Abstract: Purpose: Malignant phyllodes tumor (PT) is a fastprogression neoplasm derived from periductal stromal cells of the breast, which currently still lack effective treatment strategies. Our previous studies showed that the high density of tumor-associated macrophages (TAM) plays an important role in the malignant progression of PTs. TAMs secreted large amount of CCL18 to promote myofibroblast differentiation and invasion via binding to its receptor PIPTNM3 on myofibroblasts. Herein, we investigate the mechanism of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 53 publications
4
94
0
Order By: Relevance
“…In the phase I clinical trial testing Maraviroc as a monotherapy in advanced colorectal cancer, this translated into selective necrosis of tumor cells in liver metastases. 15 This association between CCR5 expression at the surface of macrophages, and the activation of a M2 polarization program upon its activation is supported by other reports 55 and most compellingly, the functional (re-)activation of a M1 program in TAMs using Maraviroc has been shown as well by others in other tumor entities, such as non-Hodgkin lymphoma, 56 breast cancer 55 or gastric cancer (reviewed in 57 ).…”
Section: Discussionsupporting
confidence: 56%
“…In the phase I clinical trial testing Maraviroc as a monotherapy in advanced colorectal cancer, this translated into selective necrosis of tumor cells in liver metastases. 15 This association between CCR5 expression at the surface of macrophages, and the activation of a M2 polarization program upon its activation is supported by other reports 55 and most compellingly, the functional (re-)activation of a M1 program in TAMs using Maraviroc has been shown as well by others in other tumor entities, such as non-Hodgkin lymphoma, 56 breast cancer 55 or gastric cancer (reviewed in 57 ).…”
Section: Discussionsupporting
confidence: 56%
“…For example, it has been reported that TAMs could promote prostate cancer migration through activation of the CCL22-CCR4 axis 32 . TAMs released CCL18 to further promote the aggressive phenotype of breast phyllodes tumors by enhancing and maintaining the myofibroblast differentiation and invasion in vitro and in vivo 23 . Our previous study indicated that CCL5 was one of the most abundant chemokines secreted by TAMs 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that CCL5, another member of the CC chemokine family, was a more abundant TAMs-secreted chemokine than CCL2 22 . Additionally, it has been reported that the CCL5-CCR5 axis blockage in the TME may represent a potential clinically available strategy for inhibiting human breast phyllodes tumor growth 23 . Nevertheless, the prognostic value of TAMs-secreted CCL5 for prostate cancer as well as its modulatory effect on both prostate cancer cells and PCSCs cells remain unclear and deserve further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cancer‐associated fibroblasts producing CXCL12 stimulate the migration of TAMs towards tumor‐associated vessels that may promote the extravasation of tumor cells to the bloodstream . In phyllode malignant breast tumors, a particular BC subtype, CCL5 produced by tumor cells promotes the polarisation of TAMs into IL18 + producers, via the AKT pathway leading to a positive feedback for tumor promotion and aggressiveness . Moreover under hypoxia, murine melanoma tumors secrete exosomes able to up‐regulate oxidative phosphorylation in bone marrow‐derived macrophages, inducing their polarisation towards F4/80 + CD206 high M2‐MΦ, favoring tumor development …”
Section: Discussionmentioning
confidence: 99%
“…58 In phyllode malignant breast tumors, a particular BC subtype, CCL5 produced by tumor cells promotes the polarisation of TAMs into IL18 + producers, via the AKT pathway leading to a positive feedback for tumor promotion and aggressiveness. 60 Moreover under hypoxia, murine melanoma tumors secrete exosomes able to up-regulate oxidative phosphorylation in bone marrow-derived macrophages, inducing their polarisation towards F4/80 + CD206 high M2-MΦ, favoring tumor development. 61 Outstandingly, our data suggest that tumorderived factors affect monocytes in the bloodstream of patient.…”
Section: Discussionmentioning
confidence: 99%